Influence of additives and sulphurous mazout on the quality of carbonaceous clinkery ceramic splinter/Sukepimą skatinančių priedų ir sieringo mazuto įtaka karbonatingo molio keraminės šukės kokybei - Kaminskas, Antanas; Smolianskienė, Grazina; Valiukevičius, Česlovas (Journal of Civil Engineering and Management, 1999)
The Republic of Lithuania does not possess a standard document on clinker bricks. In the standard LST 1458 clinkery and baked bricks are defined as products with water absorption lower than 6% and 5%, respectively. Lately in the world market the prices of oil and its products have been greatly reduced. Since the production of clinkery bricks consumes much more fuel than baking building bricks, it would be more economic to use mazout instead of natural gas. Mazout comprises sulphur (2.5–3.5)%, therefore on the surface of produced clinkery bricks appear there sulphatic spots, worsening the surface of products. In this study the possibilities were researched how to get clinkery ceramics from carbonaceous [CaO+MgO = (12.01–14.73)%] easily dissolved clay of Kertupis-2 quarry, selecting additives which stimulate baking and to determine the influence of sulphurous mazout on the properties of ceramic splinter. Chemical composition of Kertupis-2 clay is presented in Table 1. Mineralogical composition (Fig 1) of this clay was investigated by radiographic method and dry remnant of water extract was evaporated (Fig 2). CaCO3predominated in the dry remnant. Forming mixtures, composition of which is given in Table 2, were prepared. While investigating deformation changes of forming mass at the moment of baking, dilatometric research was carried out (Fig 3–6). Baking data of laboratorial samples from Kertupis-2 clay with various additives are presented in Table 3 depending upon baking temperature. Measurings of dust amount and gas emission into atmosphere were performed when burning orimulsion, mazout M100 and desulphurized mazout with the additive of magnesium oxide. Comparable data are presented in Table 4. Sulphur oxides present in combustion gas react with calcium combinations on the surface of ceramic splinter, resulting in white deposit of CaS04. RDX pattern presented in Fig 7 has characteristic elements of anhidrite (0.349; 0.283; 0.233) nm. Having carried out the chemical analysis on the surface layer of ceramic splinter, the determined amount of sulphur combinations was more than 2.0% (rating according to S03). In the middle layers its amount fluctuated from 0.36 to 0.66%. Having summarized the results of research the following conclusions have been drawn:1. Choosing additives stimulating baking, baked earthenware with water absorption less than 6% from Lithuanian carbonaceous easily dissolved clays were obtained. When breakage of window-pane was used as an additive, baking process began at the lowest temperature.2. Baking earthenware with sulphury mazout, >2.0% of sulphur combinations formed on the surface of ceramic splinter, and in the middle layers, which had not any contact with fuel burning products, its amount fluctuated from 0.36 up to 0.66%. Applying magnesium oxide desulphurisation way, it is possible to desulphurise burning gas of mazout up to 315.3 mg/m3 of SO2 concentration. The research has developed the possibility for ceramic industry to change natural gas into much cheaper fuel – mazout.Article in Lithuanian.First Published Online: 26 Jul 2012